Storage of ‘Elmwood’ kiwifruit in controlled atmosphere and ethylene management - Brackmann, Auri; Weber, Anderson; Both, Vanderlei; Santos, Jorge Roque Alves dos; Anese, Rogério de Oliveira (Revista de Ciências Agroveterinárias, 2012)
The aim of this work was to evaluate ‘Elmwood’ kiwifruit conservation under different controlled atmosphere (CA) conditions, with or without ethylene absorption and inhibition of ethylene action by 1-MCP. The treatments were: [1] cold storage (CS), [2] CA with 1.5 kPa O2 and 5.0 kPa CO2 plus ethylene scrubbing , [3] CA with 2.0 kPa O2 and 5.0 kPa CO2 plus ethylene scrubbing [4] CA with 2.0 kPa O2 and 5.0 kPa CO2 without ethylene scrubbing and [5] CA with 2.0 kPa O2 and 7.0 kPa CO2 plus ethylene scrubbing. Fruits from all treatments were stored for fi ve months at -0.5ºC, with and without 1.0 ppm of 1-metylcyclopropene (1-MCP). 1-MCP application, on this study, provided an uneven ripening in fruits stored in CA, with more pronounced softening of the pulp in relation to the core. The three CA conditions showed a similar effect on the kiwifruit conservation and the ethylene scrubbing delayed ripening of the fruits during storage and shelf life.